1985
DOI: 10.1159/000110221
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study to Detect Neurologic Disease in Ecuador among a Population with a High Prevalence of Endemic Goiter

Abstract: A census, uniform screening questionnaire, and simple screening neurologic examination were administered in a door-to-door survey to residents of Quiroga, Ecuador, a rural community in the Andes Mountains. The screening procedures had been pretested to assure a high level of sensitivity for detecting children and adults with major neurologic disease. A total of 1,113 participated in the study. Of these, 399 had responses or findings suggesting the presence of neurologic disease. These individuals were then exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 2 publications
(8 reference statements)
2
36
1
Order By: Relevance
“…Nevertheless, recent studies from Brazil, Chile and Ecuador show that headache is highly prevalent in these countries and imposes a large economic burden on healthcare systems stretched to their limits. As in developed countries, migraine and chronic tension-type headache are the most common subtypes of headache disorders in South America [32][33][34][35][36]. Tekle Haimanot reported that "literature on prevalence and health burden in Africa is scanty" [37].…”
Section: Influence Of Race and Geographymentioning
confidence: 99%
“…Nevertheless, recent studies from Brazil, Chile and Ecuador show that headache is highly prevalent in these countries and imposes a large economic burden on healthcare systems stretched to their limits. As in developed countries, migraine and chronic tension-type headache are the most common subtypes of headache disorders in South America [32][33][34][35][36]. Tekle Haimanot reported that "literature on prevalence and health burden in Africa is scanty" [37].…”
Section: Influence Of Race and Geographymentioning
confidence: 99%
“…Whether it is equally frequent in other cultures is less well known. There are few reports of epidemiologic studies of var ious types of headaches from other coun tries, particularly the less industrialized ones 1 Grateful acknowledgment is made for the guid ance of the late Dr. Bruce Schoenberg. [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports of epidemiologic studies of var ious types of headaches from other coun tries, particularly the less industrialized ones 1 Grateful acknowledgment is made for the guid ance of the late Dr. Bruce Schoenberg. [1][2][3][4][5]. A particular point at issue is whether the prevalence of headache or any particular variety of headache (e.g., migraine) varies with the nature of the society or with educa tional level and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant type of seizure and the percentage of treated patients also differ; in Latin America, generalized seizures are most frequent [3,6,9] , and only a minority of patients receive antiepileptic drugs (AEDs) [23] . The limited number of studies on epilepsy prevalence in Argentina revealed rates similar to those of developed countries [24,25] .…”
mentioning
confidence: 99%